Biochemical mechanisms of pallidal deep brain stimulation in X-linked dystonia parkinsonism. Issue 8 (August 2015) - Tronnier, V.M.; Domingo, A.; Moll, C.K.; Rasche, D.; Mohr, C.; Rosales, R.; Capetian, P.; Jamora, R.D.; Lee, L.V.; Münchau, A.; Diesta, C.C.; Tadic, V.; et al.
Abstract: Objective: Invasive techniques such as in-vivo microdialysis provide the opportunity to directly assess neurotransmitter levels in subcortical brain areas. Methods: Five male Filipino patients (mean age 42.4, range 34–52 years) with severe X-linked dystonia-parkinsonism underwent bilateral implantation of deep brain leads into the internal part of the globus pallidus (GPi). Intraoperative microdialysis and measurement of gamma aminobutyric acid and glutamate was performed in the GPi in three patients and globus pallidus externus (GPe) in two patients at baseline for 25/30 min and during 25/30 min of high-frequency GPi stimulation. Results: While the gamma-aminobutyric acid concentration increased in the GPi during high frequency stimulation (231 ± 102% in comparison to baseline values), a decrease was observed in the GPe (22 ± 10%). Extracellular glutamate levels largely remained unchanged. Conclusions: Pallidal microdialysis is a promising intraoperative monitoring tool to better understand pathophysiological implications in movement disorders and therapeutic mechanisms of high frequency stimulation. The increased inhibitory tone of GPi neurons and the subsequent thalamic inhibition could be one of the key mechanisms of GPi deep brain stimulation in dystonia. Such a mechanism may explain how competing (dystonic) movements can be suppressed in GPi/thalamic circuits in favour of desired motor programs. Highlights: Pallidal microdialysis is a promising intraoperative monitoring tool. High frequency stimulation results in an increase of GABA levels in the GPi. Increased GABAergic inhibitory tone of GPi neurons could be one of the key mechanisms of DBS in dystonia.